Ten-year experience with transcatheter and surgical aortic valve replacement in Finland - Mäkikallio Timo; Jalava Maina P.; Husso Annastiina; Virtanen Marko; Laakso Teemu; Ahvenvaara Tuomas; Tauriainen Tuomas; Maaranen Pasi; Kinnunen Eeva-Maija; Dahlbacka Sebastian; Jaakkola Jussi; Airaksinen Juhani; et al. (TAYLOR & FRANCIS LTD, 2022)
Aim: We investigated the outcomes of transcatheter (TAVR) and surgical aortic valve replacement (SAVR) in Finland during the last decade.
Methods: The nationwide FinnValve registry included data from 6463 patients who underwent TAVR or SAVR with a bioprosthesis for aortic stenosis from 2008 to 2017.
Results: The annual number of treated patients increased three-fold during the study period. Thirty-day mortality declined from 4.8% to 1.2% for TAVR (p = .011) and from 4.1% to 1.8% for SAVR (p = .048). Two-year survival improved from 71.4% to 83.9% for TAVR (p < .001) and from 87.2% to 91.6% for SAVR (p = .006). During the study period, a significant reduction in moderate-to-severe paravalvular regurgitation was observed among TAVR patients and a reduction of the rate of acute kidney injury was observed among both SAVR and TAVR patients. Similarly, the rate of red blood cell transfusion and severe bleeding decreased significantly among SAVR and TAVR patients. Hospital stay declined from 10.4 +/- 8.4 to 3.7 +/- 3.4 days after TAVR (p < .001) and from 9.0 +/- 5.9 to 7.8 +/- 5.1 days after SAVR (p < .001).
Conclusions: In Finland, the introduction of TAVR has led to an increase in the invasive treatment of severe aortic stenosis, which was accompanied by improved early outcomes after both SAVR and TAVR.